ACOUSTIC EMISSION IN QUARTZITE OF KRIVOY ROG OVER DEEP BOREHOLE AND GRITSTONE UNDER TERMAL INFLUENCE - ONANKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Effects of acoustic emission under thermal-mechanical strains in quartzite are investigated. Elastic waves pulses are discovered from micro fractures that of probably connected with elastic balance in quartzite.